PENGARUH EMOTIONAL DEMONSTRATION PENGGUNAAN BAHAN PANGAN LOKAL TERHADAP PENGETAHUAN IBU TENTANG PENYUSUNAN MP-ASI SEIMBANG - Sari, Meida Riza Ayu Fatika; Kusmawati, Iffah Indri; Sari, Amelya Augusthina Ayu; Sari, Atriany Nilam; Novika, Revi Gama Hatta (Universitas Muhammadiyah Mataram, 2026)
Abstract: Complementary feeding (MP-ASI) is essential for children aged 6–24 months; however, maternal knowledge regarding the preparation of balanced complementary foods remains limited. A preliminary study in Tempurharjo Village identified misconceptions about MP-ASI composition and low utilization of local food sources. This study aimed to assess the effect of the Emotional Demonstration method on improving maternal knowledge. Using a pre-experimental one-group pretest–posttest design involving 69 mothers, Wilcoxon analysis yielded a p-value of 0.000, indicating a significant effect. This method proved effective in enhancing maternal understanding and has the potential for broader application to improve complementary feeding practices and support stunting prevention efforts.Abstrak: Makanan Pendamping ASI (MP-ASI) penting bagi anak usia 6–24 bulan, namun pengetahuan ibu mengenai penyusunan MP-ASI seimbang masih terbatas. Studi pendahuluan di Desa Tempurharjo menemukan adanya miskonsepsi tentang komposisi MP-ASI serta rendahnya pemanfaatan bahan pangan lokal. Penelitian ini bertujuan menilai pengaruh metode Emotional Demonstration terhadap peningkatan pengetahuan ibu. Dengan desain pre-eksperimental one-group pretest–posttest pada 69 ibu, analisis Wilcoxon menunjukkan p = 0,000, menandakan pengaruh signifikan. Metode ini terbukti efektif meningkatkan pemahaman ibu dan berpotensi diterapkan lebih luas untuk memperbaiki praktik pemberian MP-ASI serta mendukung pencegahan stunting.